KEMUDAHAN AKSES INFORMASI LAYANAN E-RESOURCES YANG DILANGGAN UIN SUNAN KALIJAGA DALAM MEMENUHI KEBUTUHAN INFORMASI MAHASISWA MAGISTER - Daulay, Nadiah Sifa (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2024)
E-resources services are one of the information services provided by libraries to meet students' information needs. This research aims to see whether e-resources services are easy to access and meet the information needs of master's students and what efforts the library has made to help students access e-resource services to meet the information needs of master's students. Ease of access to information is seen from the indicators put forward by Wang & Strong; easy to access, easy to find, complete, up to date, and easy to operate the system. This research uses a qualitative method with a phenomenological approach. Data collection techniques were carried out by means of observation, indepth interviews and documentation. The results of this research are that the e-resources services subscribed to by the UIN Sunan Kalijaga library are easy to access and meet the information needs of master's students. And the efforts made by the library really help students in meeting the information needs of master's students.